NAD+ supplementation prevents STING‐induced senescence in ataxia telangiectasia by improving mitophagy. Issue 4 (18th March 2021) - Yang, Beimeng; Dan, Xiuli; Hou, Yujun; Lee, Jong‐Hyuk; Wechter, Noah; Krishnamurthy, Sudarshan; Kimura, Risako; Babbar, Mansi; Demarest, Tyler; McDevitt, Ross; Zhang, Shiliang; Zhang, Yongqing; et al.
Abstract: Senescence phenotypes and mitochondrial dysfunction are implicated in aging and in premature aging diseases, including ataxia telangiectasia (A‐T). Loss of mitochondrial function can drive age‐related decline in the brain, but little is known about whether improving mitochondrial homeostasis alleviates senescence phenotypes. We demonstrate here that mitochondrial dysfunction and cellular senescence with a senescence‐associated secretory phenotype (SASP) occur in A‐T patient fibroblasts, and in ATM‐deficient cells and mice. Senescence is mediated by stimulator of interferon genes (STING) and involves ectopic cytoplasmic DNA. We further show that boosting intracellular NAD + levels with nicotinamide riboside (NR) prevents senescence and SASP by promoting mitophagy in a PINK1‐dependent manner. NR treatment also prevents neurodegeneration, suppresses senescence and neuroinflammation, and improves motor function in Atm −/− mice. Our findings suggest a central role for mitochondrial dysfunction‐induced senescence in A‐T pathogenesis, and that enhancing mitophagy as a potential therapeutic intervention. Abstract : The underlying cause in most A‐T cases is complex, likely reflecting risks premature aging, multiple genetic factors, and non‐genetic (e.g., environmental, lifestyle/behavioral, and metabolic) factors. These factors can directly/indirectly cause mitophagy defects, leading to accumulation of damaged mitochondria, a major feature of ATM‐deficient animals and A‐T patients. Damaged mitochondria accumulate and release DNA into cytoplasm, which activates STING‐induced glial responses, senescence and SASP. Mitophagy induction by NR treatment maintains a healthy mitochondrial pool and prevents STING activation through efficient clearance of dysfunctional mitochondria and maintains a healthy brain.